The Value of Cross-Cultural Education in the Clinical Educator Training Process: A Viewpoint. - Gauvin, Nancy; Gregory-Martin, Kyomi (Perspectives of the ASHA Special Interest Groups, 2025)
Purpose: The purpose of this article is to highlight the need for cross-cultural education skills in the clinical education training process. This article discusses the benefits of cross-cultural education for clinical educators (CEs) who work with supervisees from cultures that differ from their own. Conclusions: CEs differ based on their cultural backgrounds and their perception of concern about the impact that cultural differences have on the supervisory process. There is a need for cross-cultural education training for speech-language pathologists who work with supervisees particularly when there are limited cultural similarities between the CEs and supervisee. Further studies are needed to assess CEs' perceptions of the supervisory process and the potential impact it has on their own biases and interactions with supervisees.